AN ALGORITHM OF IDENTIFICATION OF THE OPTIMAL COMBINATION OF INTERNAL AND EXTERNAL SOURCES OF SUPPLY FOR THE FORMATION OF THE SYSTEM OF FOOD SUPPLY OF THE ARMED FORCES IN THE ARCTIC ZONE OF RUSSIAN FEDERATION - Zheishev, Ruslan Satvaldovich; Nikitin, Yuriy Aleksandrovich (Krasnoyarsk Science, 2019)
The Arctic group of the Armed Forces of Russian Federation that is being formed now requires stable food supplies. However economic, logistic and climatic conditions of this region make the formation of the system of food supply difficult and require a solution of the problem of optimal combination of food deliveries from internal and external sources.Goal of the research: working out a method of substantiation of an optimal combination of food deliveries from external and internal sources for the system of food supply of the Armed Forces in the Arctic Zone of Russian Federation.Methods of research: analysis and synthesis, mathematical modelingResults: an economic and mathematical algorithm of formation of an optimal combination of food deliveries from internal and external sources. Формируемая в настоящее время Арктическая группировка Вооруженных Сил Российской Федерации нуждается в бесперебойном продовольственном обеспечении. Однако экономические, логистические и климатические условия этого региона затрудняют формирование системы продовольственного обеспечения и требуют решения задачи оптимального комбинирования поставок продовольствия из внутренних и внешних источников.Цель исследования: разработка методики обоснования оптимального сочетания поставок продовольствия из внешних и внутренних источников в интересах системы продовольственного обеспечения войск (сил) в Арктической зоне Российской Федерации.Методы исследования: анализ и синтез, математическое моделирование.Результаты: разработан экономико-математический алгоритм формирования оптимального сочетания поставок продовольствия из внутренних и внешних источников.